Repercussões das atividades desenvolvidas pelos projetos institucionais da UFSM no âmbito do PIBID/CAPES/MEC em escolas públicas de educação básica - Silva, Andréia Aurélio da (2012)
This research, we sought to understand the implications on Public Elementary Schools (PES) activities in the developed within the institutional subprojects PIBID/CAPES/UFSM. For this, we set out to answer the following research question: What main aspects characterize the changes in the organization and development of school work in PES involved in carrying out activities under the institutional project's PIBID/CAPES/UFSM? Due to the nature of this problem, for preparation of an appropriate response, we work with qualitative information, which qualifies our research as qualitative in nature. Information sources used in research are of three types, namely: subjects (members of management teams of PES and supervisors fellows subprojects PIBID/CAPES/UFSM 2007 and 2009 elementary school teachers), spaces (institutional events PIBID/CAPES/UFSM) and documents (subprojects PIBID/CAPES/UFSM 2007 and 2009). The instruments used to collect information in these sources were interviews, observations, and textual analysis of screenplays. The research involved 07 members of the management teams of PES, 08 supervisors fellows, 03 other subjects (who were at the same time, members of the management teams and supervisors fellows), 02 institutional events PIBID/CAPES/UFSM and 10 subprojects PIBID/CAPES/UFSM. From the analyzes we can say that the activities undertaken by the different subprojects had repercussions in every school, as caused changes on two levels. First, under the organization of school work, changes were found that due to the nature (material) and degree of involvement of professionals PES are, for the most part, superficial and duration equivalent to the subproject, as they included adding tasks to members of the management teams of schools, creation of meeting teachers for meetings of continuing education, serving students with learning difficulties. In this scope, further highlight the creation or revitalization of school spaces as a change that has the potential to continue, that is, to transcend time development subproject PIBID schools. Second, within the school organization, changes were identified that refer to insertion of new teaching methodologies as well as reformulations in pedagogical practices of teachers of the schools involved. These modifications involve changes deeper work done by their teachers, requiring reorganization of his thoughts about the concepts used and actions taken. Thus, such modifications, by their very nature, have a greater potential for survival, while the modifications presented in the first part usually have a longer restricted to the period of development of the activities of the subprojects.